A microprocessor based telemetry outstation - Lusty, John Hilary (Department of Electrical Engineering, 2016)
This thesis describes the development of a microprocessor based telemetry outstation used to collect analogue and digital data at remote sites for the Cape Town City Council's Waterworks Branch of the City Engineer's Department. It is a functional equivalent of existing vendor supplied outstations which are not microprocessor based i.e. they rely purely on hardware. It was necessary to develop these units in-house due mainly to cost considerations since the vendor supplied units were becoming increasingly expensive; furthermore, they are using obsolescent technology and the purchase of spare parts has become increasingly difficult. This latter situation has been aggravated in more recent times by the threat of sanctions. The expertise gained by the writer from the development phase has already been directly applicable to another telemetry project for the Cape Town City Council. This dramatically shortened the development time. Further projects of this nature are envisaged. The outstation collects dam level and water flow rate values and alarms at remote sites, most of them reservoirs. In addition, the flow rates are integrated with respect to time to give volumes. These quantities are transmitted back to the master station via a modem and u.h.f. tranceiver when interrogated by a master station. The development of the outstation involved a detailed analysis of the telemetry protocol between the master station and five existing outstations. A complete set of general purpose hardware modules had to be designed with future applications in mind, a software philosophy formulated, implemented and tested and extensive field testing and evaluation performed before production of sixteen units commenced. All the development work was done in the Computer Section of the City Electrical Engineer's Department in Cape Town.